Desiccation and Cracking Behaviour of Clay Under Wetting and Drying - Olude, Adebayo Iyanuoluwa (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
Cracks are formed when moisture loss in soil creates channels for water flow. This research investigates the cracking behavior of clayey soil subjected to wetting-drying cycles. Laboratory tests were performed on both natural (control soil) and bentonite added soils. Desiccation rates were observed and recorded for soil specimens using the air-dry and oven-dry approach at 60oC. Soil specimens containing different percentages of bentonite (5% and 10%) were subjected to four wetting and drying cycles. Double punch test was conducted to determine the tensile strength of natural soil. The swelling and shrinkage tests were carried out on natural soil specimens as well as examining the matric suction. Results of the desiccation method employed showed that cracks did not occur on the natural soil at any stage of the air-drying condition while in the oven-drying method, cracks were observed in the increasing drying stages. Crack dimension was quantified by using digital image processing known as ImageJ software. The results for the experimental cyclic wetting and drying indicated that the crack intensity factor, CIF increased with an increasing number of cycles. Soil water characteristic curve, SWCC of the control soil was constructed using filter paper method and the air-entry value, AEV was obtained at 31% water content. This water content obtained from the SWCC is in good harmony with the value obtained using the silica gel drying method.

ÖZ: Topraktaki nem kaybı su akışı için kanallar oluşturduğunda çatlaklar oluşur. Bu araştırma, ıslatma-kurutma döngülerine maruz kalan killi toprağın çatlama davranışını incelemektedir. Hem doğal (kontrol toprağı) hem de bentonit katkılı topraklarda laboratuar testleri yapılmıştır. 60oC'de hava ile kurutma ve fırında kurutma yaklaşımı kullanılarak toprak numuneleri için kuruma oranları gözlemlenmiş ve kaydedilmiştir. Farklı oranlarda bentonit (% 5 ve% 10) içeren toprak numuneleri dört ıslatma ve kurutma döngüsüne tabi tutulmuştur. Doğal toprağın çekme dayanımını belirlemek için çift vuruş testi yapılmıştır. Şişme ve büzülme testleri, doğal toprak numunelerinde ve ayrıca matrik emiş ölçülerek yapılmıştır. Kullanılan kurutma yönteminin sonuçları, doğal toprakta hava ile kurutma koşulunun hiçbir aşamasında çatlak oluşmadığını, fırında kurutma yönteminde ise artan kurutma aşamalarında çatlaklar olduğunu göstermiştir. Çatlak boyutu, ImageJ yazılımı olarak bilinen dijital görüntü işleme kullanılarak ölçüldü. Deneysel döngüsel ıslatma ve kurutma sonuçları, çatlak yoğunluğu faktörünün, CIF'in artan sayıda döngü ile arttığını gösterdi. Kontrol toprağının toprak su karakteristik eğrisi, SWCC'si filtre kağıdı yöntemi kullanılarak oluşturulmuş ve %31 su içeriğinde hava giriş değeri, AEV elde edilmiştir. SWCC'den elde edilen bu su içeriği, silika jel kurutma yöntemi kullanılarak elde edilen değer ile iyi bir uyum içerisindedir.
Master of Science in Civil Engineering. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2020. Supervisor: Prof. Dr. Zalihe Nalbantoğlu Sezai
Keywords: Air entry value, bentonite, crack intensity factor, desiccation, soil water characteristic curve, swelling and shrinkage, wetting and drying.; Clay Soils--Soil moisture